HUBUNGAN ANTARA CEMAS DAN DEPRESI MAHASISWA KEDOKTERAN UNIVERSITAS UDAYANA DENGAN KEINGINAN DAN HARAPAN DARI KARIR KEDOKTERAN - Putu Satya Pratiwi; Cokorda Bagus Jaya Lesmana (Universitas Udayana, 2016)
Medical education requires effort and hard work with high stress levels, and reported as a cause of burnout, anxiety, depression, and psychosocial problems. Settling on a course of study can not be separated from the underlying desires and expectations to be achieved. The aim of this study was to determine the relationship of anxiety and depression in medical students Udayana University with the desires and expectations of the medical career. This study used a cross-sectional study. The samples used were second and fourth semester students of academic year 2014/2015 in Medical Education Program, Faculty of Medicine, University of Udayana. Instruments in this study is the Hospital Anxiety and Depression Scale (HADS). Questionnaire data obtained were analyzed by One-way Analysis of Variance (ANOVA), t-test and crosstab test. The results of descriptive study are the main reason for choosing the medical faculty are ideals to be a doctor, and the greatest expectation of medical education is job satisfaction. In the analysis, it was found that the desire in choosing medical school related to levels of anxiety, with p value = 0.000. Students who chose medical school because of pressure from the outside to have higher levels of anxiety. No relationship was found between the level of depression with variable desires (p=0,487). Expectation from choosing a medical school is not associated with the level of anxiety (p=0,799) and depression (p=0,660).[c1] [AA2] [c1]satya [AA2]